From Orphan to Adoptee : U.S. Empire and Genealogies of Korean Adoption - Pate, SooJin (Book collections on Project MUSE., 2014)
Since the 1950s, more than 100,000 Korean children have been adopted by predominantly white Americans; they were orphans of the Korean War, or so the story went. But begin the story earlier, and what has long been viewed as humanitarian rescue reveals itself as an exercise in expanding American empire during the Cold War. Transnational adoption was virtually nonexistent in Korea until U.S. military intervention in the 1940s. This book identifies U.S. militarism as the condition by which displaced babies became orphans, normalised for American audiences, and detached from their past and culture.